Ontogenetic stages of Czenspinskia transversostriata (Oudemans) (Acari: Winterschmidtiidae) - Zhang, Keshi; Fan, Qing-Hai (Zootaxa, 2025)
Studies on the developmental stages of mites in the family Winterschmidtiidae are scarce. Here, we provide detailed descriptions and illustrations of the larva, protonymph, tritonymph, and adult of Czenspinskia transversostriata (Oudemans), based on individuals reared on dry yeast pellets under laboratory conditions. Comparisons of idiosomal and leg chaetotaxy among stages are also presented.